Students’ perceptions on learning, motivation, and performance through project-based learning: undergraduate students’ case - Paskalia Pradanti; Moh. Rikza Muqtada (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2023)
Project-based learning is an approach that is able to facilitate authentic learning. Authentic learning as an experiential process that prepares future educators can help the development of necessary teaching skills. Assessment of project-based learning is required to evaluate how it successfully promotes students’ learning. A survey was conducted to assess students’ perspectives on the implementation of project-based learning. Undergraduate students who enrolled in a mathematics learning strategy course at a faculty of teaching training at a university participated in the survey. Student samples responded to the questionnaire based on their video production assignment project experiences. The collected research data were then analyzed descriptively. Data analysis results suggested that project-based learning positively impacted students’ learning, motivation, and performance. As a result, future research and learning can investigate and implement project-based learning in greater depth.